Diversity in nutrient content and consumer preferences of sensory attributes of peanut (Arachis hypogaea L.) varieties in Ugandan agroecosystems - Nankya, Rose; Mulumba, John W.; Lwandasa, Hannington; Matovu, Moses; Isabirye, Brian; De Santis, Paola; Jarvis, Devra I. (MDPI, 2021)
The cultivated peanut (Arachis hypogaea L.) is one of the most widely consumed legumes globally due to its nutrient content, taste, and affordability. Nutrient composition and consumer preference were determined for twenty local farmer (landrace) and commercial peanut varieties grown in the Nakaseke and Nakasongola districts of the central wooded savanna of Uganda through sensory and laboratory evaluation. Significant differences in nutrient content (p < 0.05) among peanut varieties were found within and across sites. A significant relationship between nutrient content and consumer preference for varieties within and across sites was also realized (Wilk’s lambda = 0.05, p = 0.00). The differences in nutrient content influenced key organoleptic characteristics, including taste, crunchiness, appearance, and soup aroma, which contributed to why consumers may prefer certain varieties to others. Gender differences in variety selection were significantly related to consumer preference for the crunchiness of roasted peanut varieties (F = 5.7, p = 0.016). The results imply that selecting different varieties of peanuts enables consumers to receive different nutrient amounts, while experiencing variety uniqueness. The promotion of peanut intraspecific diversity is crucial for improved nutrition, organoleptic appreciation and the livelihood of those engaged in peanut value chains, especially for the actors who specialize in different peanut products. The conservation of peanut diversity will ensure that the present and future generations benefit from the nutritional content and organoleptic enjoyment that is linked to unique peanut varieties.